Fully coupled time domain solution for hydroelastic analysis of a floating body. (1st April 2018) - Pal, S.K.; Datta, R.; Sunny, M.R.
Abstract: A numerical method is developed to study the ship hydroelasticity problem in time domain. Boundary – Element Method (BEM) with three-dimensional transient free-surface Green function and Neumann – Kelvin approximation is used for the solution of the hydrodynamic part. The structural domain is modeled by finite element method (FEM) using 1D beam element in time domain. The coupling between BEM and FEM is made through body boundary condition in the hydrodynamic solution. Furthermore, direct integration scheme, i.e. Newmark – β method is used for obtaining the structural velocity and deformation. The efficiency and robustness of the proposed method are validated with available published results. Three different barge type structures and a large container ship are taken for the analysis. A good correspondence is observed between the proposed and reported numerical and experimental results. Also, it is observed that structural flexibility plays an important role while calculating structural deflection, shear force, bending moment etc. The developed numerical method seems to be robust, efficient and a very useful tool in predicting the hydrodynamic loads, structural deflections, shears force, bending moment etc. for flexible structure. Highlights: A direct BEM-FEM coupled method in time domain is proposed for hydroelasticity analysis. A 3D time domain panel method is used for the hydrodynamic solution. Finite element method is used to solve the structural domain. An efficient algorithm is proposed to coupled the BEM-FEM code. Proposed method showed good agreement with the published results.